2019
DOI: 10.1021/acs.joc.9b01330
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembly of Liquid Crystalline Triphenylenedicarboxythioimides

Abstract: We report the synthesis and properties of a series of novel triphenylenedicarboxyimides and thioimides (4−6) to probe the effect of thionation on the formation of columnar mesophases. These materials display broad columnar mesophases and high clearing points and self-associate in solution to form dimers. Overall, thionation improved the self-assembly in solution and led to a stabilization of the columnar mesophase. Furthermore, increasing the thionation of these materials led to a lowering of the lowest unoccu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Previous studies on imide materials have shown that thionation can be used to improve electron-accepting ability of imides by lowering the LUMO energy, producing materials with lower HOMO-LUMO gaps. 27,[46][47][48][49][50][51] We have also shown that thionation of imide containing discotic liquid crystalline compounds has only a small impact on liquid crystallinity while altering the electronic properties signicantly. 27,51 We therefore sought to explore the effect of thionation on the mesomorphic properties of compound 4.…”
Section: Results and Discusisonmentioning
confidence: 90%
See 2 more Smart Citations
“…Previous studies on imide materials have shown that thionation can be used to improve electron-accepting ability of imides by lowering the LUMO energy, producing materials with lower HOMO-LUMO gaps. 27,[46][47][48][49][50][51] We have also shown that thionation of imide containing discotic liquid crystalline compounds has only a small impact on liquid crystallinity while altering the electronic properties signicantly. 27,51 We therefore sought to explore the effect of thionation on the mesomorphic properties of compound 4.…”
Section: Results and Discusisonmentioning
confidence: 90%
“…27,[46][47][48][49][50][51] We have also shown that thionation of imide containing discotic liquid crystalline compounds has only a small impact on liquid crystallinity while altering the electronic properties signicantly. 27,51 We therefore sought to explore the effect of thionation on the mesomorphic properties of compound 4. Compound 4 was readily accessed by 6-fold thionation of 3 giving the desired product in 60% yield.…”
Section: Results and Discusisonmentioning
confidence: 90%
See 1 more Smart Citation
“…A notable structural feature of the light harvesting monomer is the thioamide group which may enable sulfur···sulfur and sulfur···π interactions within the binding modes of the supramolecular polymer . Introduction of sulfur via thionation of aromatic carboxyimides was investigated early on, and the improved optoelectronic properties upon chromophore carbonyl thionation have been recognized in previous literature. These properties linked to thionation include an increase in charge mobility, extended excited state lifetimes, and lower optical band gaps. , In addition to the desired red-shift into visible wavelengths upon thionation of UV-absorbing chromophores such as naphthalene monoamide or naphthalene diimide, triplet formation was observed in thionated sQDM with an excited state lifetime of 395 μs for the phosphorescence half-life time τ p at 77 K. , We envisaged the molecular dipole moment of the QDM scaffoldinduced by the highly polarizable thioamide groupsas a favorable feature for supramolecular interactions that could lead to dipolar antiparallel stacking along the short axis of the chromophore cores. Drastic influences of the scalar dipole moment strengths have been reported in conjunction with photocatalytic activity of chromophore assemblies by our group .…”
Section: Resultsmentioning
confidence: 99%
“…The imides were introduced by condensation of 8-10 with the appropriate amines. 26,27 Unfortunately, attempts to grow crystals suitable for X-ray diffraction of key compounds were unsuccessful.…”
Section: Design and Synthesismentioning
confidence: 99%